Digital Business Transformation: A Systematic Literature Review On Models, Strategies, And Challenges In The Digital Economy Era - Toong Hai Sam; Nuryadi Nuryadi; Komarun Zaman (CV Pena Jaya Pers, 2026)
Purpose: This study examines Indonesia’s transition toward sustainable development in achieving the 2045 Golden Indonesia Vision by analyzing the performance and challenges reflected in four major sustainability indices: the Green Economy Index (GEI), Indonesian Blue Economy Index (IBEI), Environmental Quality Index (EQI), and Regional Competitiveness Index (RCI). It aims to provide a comprehensive understanding of how these indices collectively portray sustainability progress and reveal structural gaps. Design/methodology/approach:This study employs a systematic literature review approach by synthesizing data from government reports, official publications, and academic journals. Each index is analyzed based on its conceptual framework, measurement methodology, and key findings to identify patterns, inconsistencies, and policy implications. Findings: The findings reveal a complex and sometimes contradictory picture of sustainable development in Indonesia. The GEI indicates progress mainly driven by improvements in the socio-economic dimension, while the environmental dimension remains relatively weak. The EQI demonstrates fluctuations, particularly in Marine Water Quality (MWQ), highlighting a gap between blue economy ambitions and environmental realities. The IBEI records a relatively low national score (43.98), suggesting that Indonesia’s blue economy development is still at an early stage. Furthermore, the RCI reveals significant regional disparities in competitiveness, which may hinder inclusive and balanced sustainable development. Research limitations/ implications: This study is limited to secondary data and literature-based analysis. Future research is recommended to incorporate empirical and quantitative approaches to validate the findings and explore interrelationships among indices as well as regional dynamics. Practical implications: The results highlight the need for more integrated and balanced policy strategies, particularly in strengthening environmental performance, aligning blue economy initiatives with ecological sustainability, and reducing regional disparities. Policymakers should enhance cross-sectoral coordination to achieve inclusive and sustainable national development. Originality/value: This study provides a comprehensive synthesis of Indonesia’s key sustainability indices, offering a holistic perspective that highlights inconsistencies and structural challenges often overlooked in single-index analyses.